ANALISIS HUBUNGAN FAKTOR-FAKTOR MOTIVASI KERJA DENGAN KEPUASAN KERJA KARYAWAN PELAKSANA PADA PT. PERKEBUNAN NUSANTARA III SEI MERANTI - Dhartie Sartika Novionita; Rosnita '; Evy Maharani (Program Studi Pendidikan Ekonomi Universitas Riau, 2017)
Employees and companies are two things that are related. Employees has animportant role in a company. Employees need motivation and satisfaction in workinto promote the spirit of employees in working company. The purpose of thisresearch is: 1) analyzed levels of motivation work employees implementing PTPN IIISei Meranti, 2) analyzed levels of satisfaction work employees implementing PTPNIII Sei Meranti, 3) analyzed factors motivation relations work with satisfactionemployees work implementing PTPN III Sei Meranti. This study was conducted bysurvey method from April 2016 until January 2017. Analysis the data used wasdescriptive, likert, and analysis rank spearman. The sample collection done withpurposive sampling criteria employees implementation have worked more than twoyears in PTPN III Sei Meranti. The research results show that employees whoworked at the PTPN III Sei Meranti 73,49 percent are men with the average age 43years old when 55,42 percent the level of education employees primary school, theaverae length of work employees is 20 years, 66, 27 percent having 1-3 of familiesto as people, and 73,49 percent more large salary of Rp2.000.000. motivation workemployees implementing received score 3,48 to a category motivated. Satisfactionwork employees implementing received score 3,47 to a category satisfied. The arerelationship positive (in line) between motivation working with satisfaction workemployees, it means the higher motivation work employees so satisfaction workemployees did to the higher.